Cytotoxicity of 5% Tamarindus indica extract and 3% hydrogen peroxide as root canal irrigation - Erawati Wulandari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Preparation of root canal is an important stage in endodontic treatment. During conducting preparation, it is always be followed with root canal irrigation that has aim to clean root canal from necrotic tissue remains, grind down dentin powder, micro organism, wet the root canal to make preparation process of root canal easier, and solute root canal content at area that can not be reached by equipment. Flesh of Tamarindus indica (pulpa tamarindorum) is used as traditional medicine and it contains vitamin C (antioxidant), protein, fat, glucose, etc. Previous research shows that 5% tamarindus indica extract can clean smear layer but it is more cytotoxicity to cell line BHK–21 than sterilized aquabides. Purpose: This research is to compare cytotoxicity between 5% Tamarindus indica extract with 3% H2O2 as root canal irrigation material. Method: Four teen culture cell line BHK 21 divides into 2 groups. Group 1 is treated with 3% H2O2 and Group 2 is treated with 5% Tamarindus indica extract, for about 2.5 minutes in every group. Then, living and death cell percentage is measured. Data is analyzed with independent t test with significant level of 0.05%. Result: The research showed that death cell in group 1 was 29.3% and in group 2 was 21.1%. There was a significant different (p < 0.05) between group 1 and group 2. Conclusion: Cytotoxicity of 5% Tamarindus indica extract to the cell line BHK–21 is lower than 3% H2O2.